Representing and mediating political memory through visual activism: a hermeneutic analysis of Ambara's Wiji Thukul: planting words poster - I Gusti Ngurah Tri Marutama Rai; Bambang Sunarto; Mudji Sutrisno (Gelar: Jurnal Seni Budaya, 2026)
This study examines how Ambara's Wiji Thukul: Planting Words poster represents and supports the mediation of political memory through visual activism in post New Order Indonesia. Previous studies of Indonesian action posters have primarily focused on symbolism, visual rhetoric, and political messaging, while giving limited attention to how activist posters mediate historical memory through their visual form. Using a qualitative case study design and a Ricoeurian hermeneutic approach, the study analyses the poster alongside historical documents, artist statements, and literature on Indonesian political activism. The findings show that political memory is mediated through a recurring visual structure centred on the figure of Wiji Thukul, stencil aesthetics, resistance-oriented textual fragments, agricultural imagery, and a red–black color palette. These elements organize narratives of disappearance, state violence, democratic resistance, and social justice into a coherent visual framework. The study demonstrates that activist posters function not only as commemorative artefacts but also as mnemonic media that represent historical experience and support the circulation of political memory within contemporary Indonesian political culture.